Clinical InvestigationsChanges in lower urinary tract symptoms after prostate brachytherapy - Jacobs, Bruce L.; Smith, Ryan P.; Beriwal, Sushil; Benoit, Ronald M. (Journal of Contemporary Brachytherapy, 2011)
Purpose : To further define the bothersome lower urinary tract symptoms that occur after prostate brachytherapy (PB) by evaluating patient’s responses to the individual questions of the urinary portion of the Expanded Prostate Cancer Index Composite (EPIC) survey and the AUA symptoms score in men undergoing PB. Material and methods : A longitudinal, prospective study of 170 patients who have undergone PB at a single institution was performed. All patients were asked to complete the EPIC survey pre-operatively and at 2 weeks, 4 weeks, 3 months, and 6 months post-operatively. Starting with the 75th patient in the cohort, patients were also asked to complete the AUA symptom score. Results : The pattern of changes for each question is similar for both the EPIC survey and the AUA symptom score, with a marked worsening of symptoms at 2 and 4 weeks and an improvement to baseline by 3 to 6 months. Hematuria questions had the quickest and dysuria questions had the longest return to baseline. The dysuria questions had the greatest change and the incontinence questions had the smallest change in magnitude. Obstructive symptoms had a greater magnitude of change when compared to irritative symptoms, but the irritative symptoms took longer to return to baseline. Conclusions : The present study adds to the fund of knowledge regarding the bothersome lower urinary tract symptoms which occur after PB by analyzing the individual questions of both the urinary portion of the EPIC survey and the AUA symptom score.